The electroencephalogram in metastatic brain tumors O eletrencefalograma nos tumores metastáticos do encéfalo - P. Pinto Pupo; A. Mattos Pimenta; Rosa Helena Longo; A. Alves (Arquivos de Neuro-Psiquiatria)
Sixty cases of intracranial metastatic tumors diagnosed either clinically or by neurosurgery (28 operative cases, 26 with radiological contrast examinations and 6 with clinical diagnosis only) are reported. The EEG tests had been made previously to the diagnosis of metastasis. The EEG results are analysed according to the previous impression gained from this test and are presented in 5 tables, on which the cases are divided as per the brain topography of the metastasis. The positive EEG data are analysed and the possibility of topographic diagnosis discussed. The results agree with those presented in the literature. The AA. reach the following conclusions: 1) in patients with suspect brain metastasis the normal EEG allows with great probability to exclude the possibility; 2) in patients with malignant tumor the EEG signs of involvement of the nervous parenchyma are the most important elements for positive diagnosis of brain metastasis; 3) in the cases of metastasis developing at the posterior fossa, either there were indicative signs of the process at that level or the EEG was normal; 4) the EEG signs of an irritant process at the brain cortex were less frequent and, in the majority of cases, appeared in the temporal and parietal areas; 5) the signs of involvement of the mesodiencephalic structures in tumors of the brain hemispheres appeared only when the tumor was located in the median part of the hemisphere (temporal or parietal lobes); 6) signs of depression of the basal electric brain activity in the affected areas appeared rarely and in cases of parietal or occipital tumors; 7) the electric brain activity of other areas of the involved hemisphere or in the opposite hemisphere was normal in the majority of the cases observed. Considering the results of the literature and their own the AA. believe that the EEG could be a semiological method to be used at the preoperative examinations of patients with malignant tumors, with a view at establishing the possible existence of brain metastasis even in the absence of clinical symptoms. The evidence is obviously most important for orientation of the therapy in such cases, whether surgical or not. São apresentados 60 casos de tumores metastáticos intracranianos, diagnosticados clinicamente ou pela neurocirurgia (28 casos operados, 26 com exames radiológicos contrastados e 6 com diagnóstico clínico). Os exames eletrencefalográficos tinham sido feitos previamente e na mesma época do diagnóstico e da intervenção. Os resultados do EEG, interpretados previamente ao conhecimento do diagnóstico clínico, são apresentados em 5 quadros, nos quais os casos são catalogados segundo a topografia da metástase. Os dados fornecidos pelo EEG são analisados e a possibilidade do diagnóstico topográfico é discutida. Os resultados são concordantes com os da literatura. Os AA. concluem: 1) nos pacientes com suspeita de metástase cerebral o EEG normal permite, com grande probabilidade, excluir essa possibilidade; 2) nos pacientes com tumores malignos os sinais eletrencefalagráficos indicando sofrimento do parênquima nervoso são os mais importantes para um diagnóstico afirmativo de metástase cerebral; 3) nos casos de metástases desenvolvendo-se na fossa posterior o EEG se mostra normal ou, então, revela sinais indicativos de processo nessa região; 4) os sinais eletrencefalográficos de processo irritativo no córtex cerebral foram pouco frequentes e, na maioria dos casos, apareceram nas áreas temporais ou parietais; 5) os sinais de envolvimento das estruturas mesodiencefálicas em tumores dos hemisférios cerebrais aparecem nos casos de localização na parte mediana do hemisfério cerebral (lobos temporais ou parietais); 6) os sinais de depressão da ativodade elétrica cerebral de base nas áreas afetadas aparecem raramente em casos de tumores parietais ou occipitais; 7) a atividade elétrica cerebral em outras áreas do hemisfério envolvido pelo tumor e nas do hemisfério oposto se apresentou normal na maioria dos casos. Considerando os resultados da literatura e os seus próprios os AA. pensam que o EEG é um método semiológico que deva ser usado em todos os casos de pacientes com tumores malignos e candidatos a um terapêutica cirúrgica. A evidenciação de uma metástase cerebral, por este método semiológico, evitará que o paciente seja submetido a intervenção cirúrgica penosa e inútil.